THE BODY MASS INDEX (BMI) RELATED TO MENOPAUSE SYMPTOMS - Olvinda Eka Zulfi; Sri Ratna Dwiningsih; Ilya Krisnana (UNIVERSITAS AIRLANGGA, 2021)
AbstractBackground : Menopause is a natural period in a woman's life related to hormonal changes and is marked by the cessation of menstruation in the last 12 months and can cause a wide range of sometimes bothersome menopause symptoms. That menopause symptoms associated with several risk factors such as Body Mass Index (BMI) and knowledge. The study aims to identify the relationship of BMI and knowledge with menopause symptoms in the Shafa group Padang Petok Nagari Panti Selatan. Method : This research is analitic observational research with cross sectional approach. The sampling technique was carried out by total sampling consisting of 55 respondents with inclusion criteria menopause women aged 45-65 years who have not experienced dementia, have good awareness and willing to be respondents. Data were obtained by weighing, measuring height and filling out The Menopause Rating Scale to evaluate the severity of menopause-related symptoms by respondents. Afterwards the data was analyzed by the Spearman rho test to see the association between BMI and knowledge with menopause symptoms. Result : The research shows 65,4% respondents with high BMI, 72,7% with lacking of knowledge and 60% with severe menopause symptoms. The results of the Spearman rho test showed a relationship between BMI and menopause symptoms (p value = 0.000), but there is no relationship between knowledge of menopause and menopause symptoms (p= 0,450). Conclusion : BMI related to menopause symptoms. Menopause women must monitor their weight in an effort to prevent these complaints.